FAKTOR PENYEBAB LAMANYA MAHASISWA MENYELESAIKAN SKRIPSI DI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Siska Adelina (Jurnal Ecogen, 2018)
This research aimed for: describing factor that cause of the durating of student completing the thesis in Economic Faculty on State University of Padang. The type of this research is descriptive cuantitative. Population of this researh is the student of Economic Faculty on State university of Padang generatin 2010-2013 where they are complete their thesis. Data collection’s technique with questionarie which use proportional random sampling technique. Sampel for this research is 81 student. Data analysis using descriptive analysis, and exploratory analysis factor.The result from this reseach identify cause the length of the student completing their thesis in Economic Faculty on State University of Padang, and  analysis factors being caused is psycological factors, campus environtment factors, family factors, interaction with friend factors, and  attention factors. The dominant factor of this research is psycological factors with variabels effective and efficient guidance, less discipline on guidance, more inquired, attention, guidance schedule, interested, motivation, and readiness. The dominant factor make student long to completing their thesis is quidance schedule. Keyword: Thesis Completion, Psycological Factors, Campus Environtment Factors, family factors, interaction with friend factors, and  attention factors